Low power data fusion for sensor node constrained by real time management in WSN - WANG Qin; LI Chong; WAN Ya-dong; LI Lei (Tongxin xuebao)
Compared with general data fusion algorithms that fuse different space characteristics of data generated at the same time, a time series based node level data fusion algorithm constrained by real time management was proposed to study the different time features of the same space in industrial WSNs, which can meet real time management and is a ef- ficient management way to these requirements. Theoretical analysis and experiments show that it has decreased the time of sending data, reduced 28% of the energy consumption, extended the network lifecycle, and saved the communication bandwidth.